Canadian Guidelines for Controlled Pediatric Donation After Circulatory Determination of Death—Summary Report*. Issue 11 (November 2017) - Weiss, Matthew J.; Hornby, Laura; Rochwerg, Bram; van Manen, Michael; Dhanani, ; Sonny; Sivarajan, V. Ben; Appleby, Amber; Bennett, Mary; Buchman, Daniel; Farrell, Catherine; Goldberg, Aviva; Greenberg, Rebecca; et al.
Abstract : Objectives: Create trustworthy, rigorous, national clinical practice guidelines for the practice of pediatric donation after circulatory determination of death in Canada. Methods: We followed a process of clinical practice guideline development based on World Health Organization and Canadian Medical Association methods. This included application of Grading of Recommendations Assessment, Development, and Evaluation methodology. Questions requiring recommendations were generated based on 1) 2006 Canadian donation after circulatory determination of death guidelines (not pediatric specific), 2) a multidisciplinary symposium of national and international pediatric donation after circulatory determination of death leaders, and 3) a scoping review of the pediatric donation after circulatory determination of death literature. Input from these sources drove drafting of actionable questions and Good Practice Statements, as defined by the Grading of Recommendations Assessment, Development, and Evaluation group. We performed additional literature reviews for all actionable questions. Evidence was assessed for quality using Grading of Recommendations Assessment, Development, and Evaluation and then formulated into evidence profiles that informed recommendations through the evidence-to-decision framework. Recommendations were revised through consensus among members of seven topic-specific working groups and finalized during meetings of working group leads and the planning committee. External review was provided by pediatric, critical care, and critical care nursing professional societies and patient partners. Results: We generated 63 Good Practice Statements and seven Grading of Recommendations Assessment, Development, and Evaluation recommendations covering 1) ethics, consent, and withdrawal of life-sustaining therapy, 2) eligibility, 3) withdrawal of life-sustaining therapy practices, 4) ante and postmortem interventions, 5) death determination, 6) neonatal pediatric donation after circulatory determination of death, 7) cardiac and innovative pediatric donation after circulatory determination of death, and 8) implementation. For brevity, 48 Good Practice Statement and truncated justification are included in this summary report. The remaining recommendations, detailed methodology, full Grading of Recommendations Assessment, Development, and Evaluation tables, and expanded justifications are available in the full text report. Conclusions: This process showed that rigorous, transparent clinical practice guideline development is possible in the domain of pediatric deceased donation. Application of these recommendations will increase access to pediatric donation after circulatory determination of death across Canada and may serve as a model for future clinical practice guideline development in deceased donation.